The trouble with ed schools - Labaree, David F (Yale Univ. Press, 2004)
American schools of education get little respect. They are portrayed as intellectual wastelands, as impractical and irrelevant, as the root cause of bad teaching and inadequate learning. In this book a sociologist and historian of education examines the historical developments and contemporary factors that have resulted in the unenviable status of ed schools, offering valuable insights into the problems of these beleaguered institutions.David F. Labaree explains how the poor reputation of the ed school has had important repercussions, shaping the quality of its programs, its recruitment, and the public response to the knowledge it offers. He notes the special problems faced by ed schools as they prepare teachers and produce research and researchers. And he looks at the consequences of the ed school's attachment to educational progressivism. Throughout these discussions, Labaree maintains an ambivalent position about education schools-admiring their dedication and critiquing their mediocrity, their romantic rhetoric, and their compliant attitudes.